The development of health literacy in patients with a long-term health condition: the health literacy pathway model - Edwards Michelle; Wood Fiona; Davies Myfanwy; Edwards Adrian (BMC, 2012)
Abstract Background Inadequate health literacy has been associated with poor management of long-term health conditions and has been identified as a key social determinant of health outcomes. However, little is understood about how health literacy might develop over time or the processes by which people may become more health literate. Our objectives were to describe how patients with a long-term condition practice health literacy in the management of their health and communication with health professionals, how they become more health literate over time and their experience of using health services. We also sought to identify and describe the motivations, facilitators and barriers in the practice of health literacy in healthcare consultations. Methods We designed a longitudinal qualitative study using serial interviews with 18 participants to explore their experiences of learning to manage their condition and their experiences of health literacy when participating in healthcare processes. Participants were recruited from patient education programmes and were interviewed three times over a period of 9 months. A framework approach was used to analyse data. Results A model is presented that illustrates the development of health literacy along a trajectory that includes the development of knowledge, health literacy skills and practices, health literacy actions, abilities in seeking options and informed and shared decision making opportunities. Motivations and barriers to developing and practising health literacy skills partly reflected participants' characteristics but were also influenced by health professionals. Some participants developed their health literacy to a point where they became more involved in healthcare processes (including informed and shared decision-making). Conclusions Patients with a long-term condition can develop health literacy skills over time and put their skills into practice in becoming more active in healthcare consultations. Our findings have implications for developing health literacy interventions aimed at patient involvement in healthcare processes and improved self-management of long-term conditions.